Linking the theory and practice: self-reflections on technology-integrated English grammar teaching. Issue 2 (4th March 2023) - Ilmi, Ma'rifatul; Drajati, Nur Arifah; Putra, Kristian Adi
ABSTRACT: This narrative study aimed at exploring how one pre-service English teacher linked theories into practice through reflective practice. To record the teacher's reflection, we gathered the teacher's video-based reflective diaries. The data were thematically analysed using Farrell's framework for foreign language teachers' self-reflection: theories and practice. The results revealed two significant points from the teacher's reflection: (1) the pre-service teacher had a conscious raise on the affordance of theories-in-use (i.e. experience-based knowledge); and (2) the pre-service teacher realized that technology is a tool and a teacher has a crucial role in teaching to achieve the learning goals. It implied that reflective practice stimulated teachers to make sense of their experiences, leading them to the development of their teaching knowledge and performance. The implications of the present study are discussed.